2008
DOI: 10.1002/imhj.20191
|View full text |Cite
|
Sign up to set email alerts
|

Six‐week postpartum maternal depressive symptoms and 4‐month mother–infant self‐ and interactive contingency

Abstract: Associations of 6-week maternal depressive symptoms [Center for Epidemiological Studies Depression Scale (CES-D)] with 4-month mother-infant self-and interactive contingency patterns during face-to-face play were investigated in 132 dyads. Self-and interactive contingency (auto-and lagged cross-correlation, respectively) were assessed by multilevel time-series analysis. Infant and mother gaze, facial and vocal affect, touch, and spatial orientation behaviors were coded second-by-second from splitscreen videota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(186 citation statements)
references
References 54 publications
11
168
1
3
Order By: Relevance
“…Maternal depression has been associated with diminished maternal ability to coordinate face-to-face interactions and less affective behavioural matching in general, but heightened matching of negative affective states [25,26,27,28]. Beebe et al [29] found maternal interactive coordination to be either excessive (for affect) or insufficient (for gaze and touch) in mothers with high levels of depressive symptoms (vs. low levels). On the other hand, Cohn et al [30] found no differences in contingencies between post-partum depressed and non-depressed dyads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal depression has been associated with diminished maternal ability to coordinate face-to-face interactions and less affective behavioural matching in general, but heightened matching of negative affective states [25,26,27,28]. Beebe et al [29] found maternal interactive coordination to be either excessive (for affect) or insufficient (for gaze and touch) in mothers with high levels of depressive symptoms (vs. low levels). On the other hand, Cohn et al [30] found no differences in contingencies between post-partum depressed and non-depressed dyads.…”
Section: Introductionmentioning
confidence: 99%
“…Affective behavioural matching is a dyadic measure of interactive coordination referring to parent and infant being in the same affective state at the same time and seems to indicate the quality of dyadic interaction [35,36]. Regarding coordination in mother-infant interaction in general, research suggests that moderate rather than high or low levels of dyadic matching are related to more optimal outcomes, such as attachment security [for an overview, see [13,29]. Recent micro-analytic studies revealed only moderate proportions of matching in normal play interactions from as low as 12% [37] to 30-40% of the time [38].…”
Section: Introductionmentioning
confidence: 99%
“…Fraiberg [19] described the Freezing behavior as an early defense mechanism arising from the age of four months, when the child is faced with a strong experience of helplessness. This was then described by Beebe [20] as the precursor of attachment disorganization.…”
Section: Open Accessmentioning
confidence: 94%
“…4 Offspring born to women with untreated antenatal depression may experience poorer growth, increased risk of infection, altered stress response, and more difficult temperaments. 5,6 Untreated maternal postpartum depression can adversely affect mother-infant interactions 7 and increase the risk of emotional, cognitive, and behavioral problems in offspring. 8 Despite its high prevalence, the risks of untreated symptoms, and opportunities for contact with healthcare providers, depression is grossly underdetected during routine perinatal care.…”
mentioning
confidence: 99%